1979
DOI: 10.1007/bf01963325
|View full text |Cite
|
Sign up to set email alerts
|

Substance P in medullary carcinoma of the thyroid

Abstract: High levels of substance P-like immunoreactivity were demonstrated by radioimmunoassay in the plasma and tumour of a patient with a medullary carcinoma of the thyroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…Our results corroborate earlier findings indicating that serotonin and TK are often expressed in the same cell (1,28,29). Previously, focal SP expression had been described in a minor subset of medullary thyroid carcinoma and pheochromocytomas (8)(9)(10)30). In our study, TK-IR was not found in nonserotonin-producing endocrine tumors; however, our sample population is too small to rule out the existence of other TK-IR endocrine tumors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results corroborate earlier findings indicating that serotonin and TK are often expressed in the same cell (1,28,29). Previously, focal SP expression had been described in a minor subset of medullary thyroid carcinoma and pheochromocytomas (8)(9)(10)30). In our study, TK-IR was not found in nonserotonin-producing endocrine tumors; however, our sample population is too small to rule out the existence of other TK-IR endocrine tumors.…”
Section: Discussionsupporting
confidence: 92%
“…TKs have also been found in other endocrine tumors, such as appendix carcinoids (5), serotonin-producing lung carcinoids (6), ovarian carcinoids (7), medullary carcinoma of the thyroid (8,9), and in pheochromocytomas (10).…”
Section: Introductionmentioning
confidence: 99%
“…There was, however, marked reduction in the transit time of colonic contents [58]. Prostaglandins E2 and F2α, serotonin, and substance P are raised in patients with medullary thyroid cancer [59,60] and have been postulated as being involved in the pathogenesis of the cancer-associated diarrhoea [58]. Currently, it is thought that the cause of the diarrhoea may vary from one individual to another; prostaglandins, serotonin, and calcitonin do remain the likely culprits though [61].…”
Section: Medullary Thyroid Cancer and The Gutmentioning
confidence: 92%
“…S juponicum has been linked with hepatoma [106,111,112,116] and S interculutum has been associated with induced bladder cancers [27,101]. The majority of available information, however, involves S hematobiurn, which has been correlated with a number of malignancies including hydronephrosis [ 1181, ovarian teratoma [68], and bladder cancer [14,74,77,95,99,100,102,110,112,126].…”
Section: Cancer and Schistosomiasismentioning
confidence: 99%